Two Orthogonal Halogen‐Bonding Interactions Directed 2D Crystalline Supramolecular J‐Dimer Lamellae. Issue 20 (12th March 2020) - Su, Meihui; Yan, Xiaosa; Guo, Xia; Li, Quanwen; Zhang, Yushi; Li, Changhua
Abstract: Dye assemblies exhibit fascinating properties and performances, both of which depend critically on the mutual packing arrangement of dyes and on the supramolecular architecture. Herein, we engineered, for the first time, an intriguing chlorosome‐mimetic 2D crystalline J‐dimer lamellar structure based on halogenated dyes in aqueous media by employing two distinct orthogonal halogen‐bonding (XB) interactions. As the only building motif, antiparallel J‐dimer was formed and stabilized by single π‐stacking and dual halogen⋅⋅⋅π interactions. With two substituted halogen atoms acting as XB donors and the other two acting as acceptors, the constituent J‐dimer units were linked by quadruple highly‐directional halogen⋅⋅⋅halogen interactions in a staggered manner, resulting in unique 2D lamellar dye assemblies. This work champions and advances halogen‐bonding as a remarkably potent tool for engineering dye aggregates with a controlled molecular packing arrangement and supramolecular architecture. Abstract : An intriguing 2D lamellar dye‐assembly with distinct dye organization in aqueous media driven by two orthogonal X⋅⋅⋅π and X⋅⋅⋅X halogen‐bonding interactions was constructed. As the only building motif, antiparallel J‐dimer was formed and stabilized by single π‐stacking and dual X⋅⋅⋅π interactions. The constituent J‐dimer units were linked by quadruple highly directional X⋅⋅⋅X bonds in a staggered manner, resulting in the unique 2D dye‐lamellae (see figure).